Unveiling gender imbalances among PhD students: early inequalities in productivity and impact influenced by supervisor-student gender combinations - Antfolk, Maria (Frontiers in Education, 2025)
IntroductionGender imbalances in academia are found globally. Even though women earn the same rate of PhD degrees, the gender imbalance becomes increasingly prominent at higher academic levels. Several reasons have been proposed for these differences, including family responsibilities, disparities in the number and size of grants awarded, invitations to present at conferences, and differences in promotions and grant allocations, all favoring men. However, these factors should be less pronounced or even absent at the PhD student level.MethodThis paper investigates whether a gender imbalance exists in scientific production and research impact, measured by the number of publications, citations, and overall publication impact, among a cohort of Swedish medical and health science PhD students. It also explores whether this possible difference is further influenced by the gender of the PI.ResultsThe results show significant differences in PhD student productivity depending on both the gender of the student and the PI, evident even at this early career stage.DiscussionThe results suggest a consistent gender pattern where female PhD students with female PIs are less productive and have a lower research impact, and PhD students with female PIs receive fewer citations.